2022
DOI: 10.9734/ajr2p/2022/v6i4125
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Analysis of Noise Levels: A Study of Selected Pubs in Calabar, Nigeria

Abstract: This research involves the assessment of noise levels in pubs operating in Calabar, Nigeria, to investigate their compliance with the permissible noise level recommended by the National Environmental Standards and Regulations Enforcement Agency (NESREA), Nigeria. A Bam and Kom (BK) Precision 732 digital sound level meter placed on a tripod was used for the measurement of noise levels for three consecutive months, from 6:00pm to 10:00pm. The measured data were subjected to descriptive statistics using excel spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Noise is an undesirable and annoying sound which come in the form of environmental pollution and it is a source of stress. When noise is loud, it becomes harmful and creates negative impact within the environment [1,2,3,4]. Noise is dangerous to health and well-being on people within the community [5].…”
Section: Introducutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise is an undesirable and annoying sound which come in the form of environmental pollution and it is a source of stress. When noise is loud, it becomes harmful and creates negative impact within the environment [1,2,3,4]. Noise is dangerous to health and well-being on people within the community [5].…”
Section: Introducutionmentioning
confidence: 99%
“…Emmanuel et al [4] reported "the assessment of noise levels in pubs within Calabar, Nigeria. The work lasted for three consecutive months.…”
Section: Introducutionmentioning
confidence: 99%